Real-world treatment patterns for patients with non-infectious uveitis in Japan: a descriptive study using a large-scale claims database (J-CAT study) - Sentaro Kusuhara; Koh-Hei Sonoda; Toshikatsu Kaburaki; Tachie Fujita; Saki Katayama; Misako Makishima; Takao Nakamura; Mariko Nio; Takashi Omoto; Yukari Matsuo-Tezuka; Tomoki Yoshizaki; Kensuke Sasaki; et al. (Journal of Ophthalmic Inflammation and Infection)
Abstract Purpose Non-infectious uveitis (NIU) can arise from various inflammatory disorders and can cause vision loss. Patients with mild NIU are typically treated with corticosteroid eye drops to reduce intraocular inflammation; however, other local/systemic treatments (corticosteroids, immunosuppressants, biologics) may be required for moderate-to-severe NIU, which may cause ocular complications. Here, we investigated real-world treatment patterns for NIU in Japan. Methods Patients were selected from a large, Japanese insurance claims database using International Classification of Diseases, Tenth Revision codes; diagnosis of NIU was confirmed via ophthalmological examination (October 2016–October 2023). Sankey diagrams were used to describe treatment transitions. Post-treatment ocular complications, potentially related surgeries, and fundus findings associated with uveitis were determined. Results The majority of patients (68.7%; 37,869/55,091) were treated with corticosteroid eye drops only for mild NIU; 19.0% (10,449/55,091) were given other treatments for moderate-to-severe NIU, mostly oral corticosteroids (7,473/10,449) and posterior sub-Tenon’s corticosteroid injections (1,636/10,449). In patients treated with corticosteroids orally or via sub-Tenon’s injections, common transitions were to corticosteroid eye drops or censor (end of treatment/dataset or insurance withdrawal). A higher incidence of treatment-related ocular complications and potentially related surgeries (including glaucoma) was observed during the first year of NIU treatment compared with subsequent years (for moderate-to-severe NIU, estimated incidence of prescription of glaucoma drugs was 106 per 1,000 person-years [at 1 year], 73 per 1,000 person-years [at 2 years], and 52 per 1,000 person-years [at 5 years]). Conclusion Our comprehensive analysis of a large claims database included all prescribed medications and medical procedures (including local injections) for NIU treatment in Japan up to October 2023. Although corticosteroids are a mainstay of NIU treatment in Japan, we found that a number of treatments for moderate-to-severe NIU, other than corticosteroid eye drops, are frequently used in combination with or when switching from corticosteroid eye drops. These findings are of importance when assessing the treatment landscape and may help identify unmet clinical needs in patients with NIU.